Uniqueness of solutions of mixed problems and the Cauchy problem for parabolic equation of high order with nonrestricted coef¬ficients - Akulov , V. F.; Shishkov , A. E. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
New uniqueness classes of generalized solutions (generalized Tacklind classes) of initial-boundary-value problems are found for linear and quasilinear divergent parabolic equations of high order with coefficients increasing at infinity.